A large triaxial apparatus for the study of granular materials under repeated loading used at LNEC - Correia, A. Gomes (1996)
The improvement of analytical road pavement and railway infrastructure design methods requires a rational study of the mechanical behaviour of the constituent materials. The repeated load triaxial apparatus is one of the most common and useful tools for determining the parameters used in these design methods. This paper presents a description of a repeated load triaxial apparatus designed to test unbound granular materials of up to 0/60 gradings. The importance of the compacted density in the behaviour of these materials necessitates a laboratory compaction method that reproduces the in-situ conditions. Consequently a method of compaction and control of the density is also presented. By using this apparatus the most common parameters used in analytical pavement design (resilient modulus and Poisson’s ratio) are acquired. This is illustrated by testing a 0/20 graded crushed granite used as base course for road construction. This test apparatus may also be used to investigate the permanent deformation characteristics of base course materials.